Simultaneous Discordant B-Lymphoblastic Lymphoma and Follicular Lymphoma: Lymphoblastic Transformation With MYC Translocation. Issue 2 (11th September 2020) - Fujimoto, Ayumi; Ikejiri, Fumiyoshi; Arakawa, Fumiko; Ito, Shunsuke; Okada, Yusuke; Takahashi, Fumimasa; Matsuda, Shinichiro; Okada, Takahiro; Inoue, Masaya; Takahashi, Tsutomu; Miyake, Takaaki; Maruyama, Riruke; et al.
Abstract: Objectives: We report a rare case of B-lymphoblastic lymphoma (B-LBL) and low-grade follicular lymphoma (FL) identified concurrently in biopsies from different sites at the initial diagnosis in a 39-year-old man. The clonal relationship between the 2 histologic subtypes was investigated. Methods: A diagnosis of FL grade 1/2 (low grade) was made by bone marrow (BM) biopsy. B-LBL was identified in biopsies from the testis and pancreas. Cytogenetic and molecular analyses were performed to investigate their clonal relationship. Results: Interphase fluorescence in situ hybridization analyses and G-banding karyotype analyses identified the BCL2-IGH and MYC-IGH translocation in tumor cells from both the BM and testis. The tumor cells from the BM and testis shared the same IGH VDJ usage and a high degree of somatic mutations. These findings suggest that acquisition of MYC gene rearrangement is a critical event for lymphoblastic transformation of FL. Of note, the presence of intraclonal diversity in the B-LBL sample further suggests an earlier or concurrent event of MYC translocation than the somatic IGH mutation in the germinal center and the dedifferentiation of lymphoma cells to a precursor stage of B-cell development. Conclusions: B-lymphoblastic transformation of FL can occur with MYC gene rearrangement.